Temperature-responsive Poly(acrylamide-co-N-isopropyl acrylamide) Hydrogel: Synthesis, Characterization, and Sorption Application - Tasar, Seyda; Orhan, Ramazan (Polymer Soc Korea, 2020)
Acrylamide-based hydrogels were used to remove cationic Basic Blue 3 (BB3) dye from aqueous solutions, in this study. First, acrylamide-based hydrogel was synthesized and characterized using SEM, FTIR and swelling analysis. The effects of various parameters were investigated to determine the removal of the BB3 dye from aqueous solutions. The sorption yield of BB3 dye of the hydrogel was determined to be 99%. The desorption efficiency was found to be above 90%. The sorption experimental data were evaluated using applying the Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich (D-R) isotherm models. It was determined that the Langmuir was more suitable for isotherm the process. The maximum sorption capacity was calculated as 28.3 mg/g. Pseudo first order, pseudo second order, intraparticle diffusion, and Endovich kinetic models were used to calculate the kinetic parameters. It was concluded that the pseudo second-order kinetic model was described by the adsorption data very well.
Keywords: hydrogel; swelling ratios; sorption; kinetic and thermodynamic evaluation